2007 European Microwave Integrated Circuit Conference 2007
DOI: 10.1109/emicc.2007.4412653
|View full text |Cite
|
Sign up to set email alerts
|

SiGe millimeter-wave dynamic frequency divider with enhanced sensitivity incorporating a transimpedance stage

Abstract: Abstract-A Si/SiGe bipolar dynamic frequency divider designed for 77GHz/79GHz automotive radar is presented, which uses a transimpedance amplifier topology to improve sensitivity and operational bandwidth. Capable of operation for input frequencies from 25 GHz up to 93 GHz, the divider consumes only 35 mA at 5 V supply voltage and has a very compact die area of 295 x 475 µm 2 . In addition, measurements show that the divider operates in the full radar frequency band (76 GHz-81 GHz) up to a temperature of 100°C. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Ⅲ. 동적 주파수 분할기 설계 앞 절에서의 주파수 분할기 동작을 검증하기 위하여 1.4 GHz 입력 주파수에 대해 700 MHz 출력을 내는 1/2 주파수 분할기를  m CMOS 모델을 이용하여 설계 하였다 [6], [7] . …”
Section: 이에 따라 본 논문에서는 주파수 분할기를 통한 변조unclassified
“…Ⅲ. 동적 주파수 분할기 설계 앞 절에서의 주파수 분할기 동작을 검증하기 위하여 1.4 GHz 입력 주파수에 대해 700 MHz 출력을 내는 1/2 주파수 분할기를  m CMOS 모델을 이용하여 설계 하였다 [6], [7] . …”
Section: 이에 따라 본 논문에서는 주파수 분할기를 통한 변조unclassified
“…Fig. 1 shows a relation between the operation frequency, locking range, and DC power consumption for recently reported Si-based ILFDs and dynamic FDs that operate at mm-wave bands (static FDs are not included due to lack of sufficient data points at this frequency range) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The plot clearly shows the expected tendency: dynamic FDs show wide locking ranges but only at the expense of huge power dissipation, while ILFD can reach higher frequencies with much smaller DC power although the locking range is limited.…”
Section: Types Of Frequency Dividersmentioning
confidence: 99%
“…1. Reported operation frequency range of various Si-based frequency dividers [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. of 1/(2•T D ) at the same location for each stage will result in the divide-by-N function.…”
Section: Types Of Frequency Dividersmentioning
confidence: 99%
“…It receives its input signal from the output of the first common-collector stage, improving the isolation between the output and the feedback loop. The use of simple emitter followers was preferred in order to strongly reduce the chip area and the power consumption [3]. Simulation showed that this topology was perfectly adequate in terms of output power, sensitivity and bandwidth of operation, when combined with the transimpedance amplifier stage in the loop.…”
Section: Design Philosophymentioning
confidence: 99%